2018
DOI: 10.25077/jka.v6i3.747
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antenatal Care dengan Kejadian Bayi Berat Lahir Rendah pada Ibu Aterm di RSUP Dr. M. Djamil Padang

Abstract: Bayi Berat Lahir Rendah (BBLR) dipengaruhi banyak faktor. Semua faktor dapat dicegah dan dideteksi secara dini melalui kunjungan antenatal care (ANC) yang lengkap dari segi kuantitas dan pelayanan yang berkualitas. Tujuan penelitian ini adalah menentukan hubungan antenatal care dengan kejadian bayi berat lahir rendah di RSUP Dr. M. Djamil Padang. Jenis penelitian ini merupakan studi analitik dengan desain cross sectional, dilakukan bulan Juni hingga Oktober tahun 2015. Populasi adalah rekam medik seluruh ibu h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This was in accordance with research conducted in Padang, mothers with less than four ANC visits were more likely to give birth to LBW babies compared to mothers with four ANC visits. 23 Similarly, studies conducted in India 18 and China 8 also stated that a comprehensive antenatal examination was associated with a reduced risk of LBW in infants. Studies conducted in Rwanda, 24 Ethiopia, 12,16,17,25 and Sri Lanka 11 found that lack of ANC visits was associated with low infant weight.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with research conducted in Padang, mothers with less than four ANC visits were more likely to give birth to LBW babies compared to mothers with four ANC visits. 23 Similarly, studies conducted in India 18 and China 8 also stated that a comprehensive antenatal examination was associated with a reduced risk of LBW in infants. Studies conducted in Rwanda, 24 Ethiopia, 12,16,17,25 and Sri Lanka 11 found that lack of ANC visits was associated with low infant weight.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with research conducted in Padang, mothers with less than four ANC visits were more likely to give birth to LBW babies compared to mothers with four ANC visits. 23 Similarly, studies conducted in India 18 and China 8 also stated that a comprehensive antenatal examination was associated with a reduced risk of LBW in infants. Studies conducted in Rwanda, 24 Ethiopia, 12,16,17,25 and Sri Lanka 11 found that lack of ANC visits was associated with low infant weight.…”
Section: Discussionmentioning
confidence: 99%